Pemantauan Kesehatan Ibu dan Anak Melalui Jejaring Peduli KIA (Rindu KIA) - Nuraisya, Wahyu (STIKES dan AKZI Karya Husada Kediri, 2024)
There's a delay in reaching the pregnant mother K1 causing the information or data of pregnant mothers to disappear. Cadets as the length of the hand of the maid are enabled to perform screening filling of the Pudji Rohyati Score Card (KSPR). This dedication activity is carried out using mother and child health monitoring material Through health of both mother and child Care Network which discusses early detection of high-risk pregnancies and how to fill KSPR. Used media are power point, laptop, mic, KSPR and LCD. The event was held in the village hall of Gadungan UPTD Working Area Puskesmas Wates Kediri District on March 4-6 2024. The target of the activity is the target of 15 people. The level of knowledge and ability of cadres in carrying out KSPR filling on most post test results there was an increase of 46.5% from the category enough to be good after given socialization and simulation of 88.5%. Achievement of the purpose is the success of the implementation of devotional activities. The cross-sectoral and cross-programmatic cooperation between cadres, midwives and Puskesmas Wates is very supportive in efforts to detect high-risk pregnancies early in order to maintain mother and child health.